PELATIHAN KETERAMPILAN GURU MEMBUAT SLIDE PRESENTASI POWERPOINT INTERAKTIF DI SMPN SATAP 8 PALANGKA RAYA - Lestiani, Winda; Setiawati, Nani; Thomas, Orbit; Tarigan, Ima Pinensi BR (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This PKM-PM was held at SMPN SATAP 8 Palangka Raya, Tumbang Rungan Village, Kec. Pahandut, Palangka Raya City, Central Kalimantan Province. The geographical condition of SMPN SATAP 8 Palangka Raya is on the Tumbang Rungan road with an area of 1,035 M². The distance from Palangka Raya University to SMPN SATAP 8 Palangka Raya is 13.4 Kilometers. This school is located within the work area of the Palangka Raya City Education Office, Central Kalimantan Province. SMPN SATAP 8 Palangka Raya has 12 teachers with civil servant status based on observations, while the problems that can be encountered in this area are the lack of learning media used by teachers in teaching, in addition to the lack of computer laboratory facilities as an effort to improve skills in utilizing technology. Through training, teachers can apply and use the skills that have been trained to facilitate their work in the administrative and academic fields at school. The expected output of this service is that teachers can apply and use the skills that have been trained to create and develop interesting and interactive teaching materials through the Powerpoint application, as well as improve the skills of teachers in utilizing technology-based media as a form of professionalism at work.